Total quality management in educational institutions (Journal of the College of Basic Education, 2023)
The need for research calls for aspiration to keep abreast of educational developments and developments and to achieve excellenceThe performance and operations of educational institutions.The importance comes from the increasing interest in total quality management, as it has become a basic function for every companyorganization and management philosophy; And a lifestyle to obtain a competitive advantage that enables it to survive and continue to existIn light of the successive and rapid changes that the world is witnessing, so that it has become tantamount to permanence and survival for allorganization or institution